Peningkatan Pengetahuan Kesehatan Gigi pada Siswa Sekolah Dasar Melalui Penggunaan Media Busy Book: Pendekatan Menarik dalam Pendidikan Kesehatan Gigi - Liasari, Ira; Priyambodo, R. Ardian; Utari, Nanda; Nur Aida, Wanda (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Dental and oral health issues, such as dental caries and periodontal diseases, can cause problems in children. Therefore, it is important to provide effective dental health education and promotion to children, especially at the elementary school level. This research aims to examine the effectiveness of dental health education using busy book media in improving knowledge about dental health among students of SD Inpres 12/79 Batulappa, Patimpeng District, Bone Regency. The study utilizes a one-group pretest-posttest design. Data on dental health knowledge was collected through questionnaires before and after the intervention. Data analysis involved statistical tests to compare the differences in knowledge before and after the intervention. The results of the study indicate that after receiving education using the busy book media, students experienced a significant improvement in their knowledge of dental health. Based on these findings, it can be concluded that dental health education using busy book media is effective in enhancing knowledge about dental health among students of SD Inpres 12/79 Batulappa, Patimpeng District, Bone Regency. The use of busy book media can serve as an effective and engaging alternative to enhance children's knowledge of dental health. It is recommended to integrate dental health education using this media into school programs as part of holistic and sustainable dental health promotion efforts.